Scalp Nerve Block for External Ventricular Drain in a Geriatric Patient with Anticipated Difficult Airway: A Case Report - Komang Ady Widayana; Andika Metrisiawan (Jurnal Anestesiologi dan Terapi Intensif, 2026)
Emergency neurosurgical procedures in geriatric patients with an anticipated difficult airway pose major anesthetic challenges due to limited physiological reserve and the risk of hemodynamic instability during general anesthesia. We report the use of a scalp nerve block (SNB) as the primary anesthetic technique for urgent external ventricular drain (EVD) placement in a female patient in her mid-70s with intracerebral hemorrhage and obstructive hydrocephalus. She presented with  decreased consciousness and a LEMON score of 6, indicating a high likelihood of difficult airway, and was classified as American Society of Anesthesiologists (ASA) physical status IIIE. Given the elevated intracranial pressure and anticipated difficulty in airway management, SNB with lidocaine and dexmedetomidine as an adjuvant was performed under standard monitoring. The procedure was completed uneventfully, with stable hemodynamics and adequate analgesia, without the need for airway manipulation or conversion to general anesthesia. This case highlights that SNB may be a feasible alternative anesthetic approach for selected high-risk geriatric patients undergoing EVD placement, particularly when airway intervention may be hazardous or when advanced airway and critical care resources are limited. Further reports and larger studies are required to determine safety and generalizability.